2000
DOI: 10.1177/154193120004402230
|View full text |Cite
|
Sign up to set email alerts
|

Upper Extremity Disorders in Professional Female Milkers

Abstract: The prevalence of and the impact of selected factors on self-reported musculoskeletal complaints in Swedish female milkers with special reference to symptoms in the upper extremities were investigated using on data from mail-in surveys. An agricultural study group was formed of three subgroups: 161 active milkers, 108 non-milkers and 62 ex-milkers, women who had been milkers earlier but were no longer doing that kind of work. In the course of the analysis these subgroups were compared with each other and also,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Upper extremity injuries have plagued dairy farmers with 27% of all injuries being attributed to this region [Pratt et al, 1992] and tobacco farmers with 25% [Struttmann and Reed, 2002]. Based on a Swedish study, hand and wrist injuries are also prevalent on dairy farms with 51% of female dairy farmers suffering an injury [Stal, 2000]. Shoulder pain in the previous year was found to be greater in farming (14%) than either other manual labor (9.7%) or non-manual labor (7.1%) jobs [Walker-Bone and Palmer, 2002].…”
Section: Upper Extremities (Hands Wrists Elbows Arms and Shoulders)mentioning
confidence: 99%
See 1 more Smart Citation
“…Upper extremity injuries have plagued dairy farmers with 27% of all injuries being attributed to this region [Pratt et al, 1992] and tobacco farmers with 25% [Struttmann and Reed, 2002]. Based on a Swedish study, hand and wrist injuries are also prevalent on dairy farms with 51% of female dairy farmers suffering an injury [Stal, 2000]. Shoulder pain in the previous year was found to be greater in farming (14%) than either other manual labor (9.7%) or non-manual labor (7.1%) jobs [Walker-Bone and Palmer, 2002].…”
Section: Upper Extremities (Hands Wrists Elbows Arms and Shoulders)mentioning
confidence: 99%
“…Cutting grapes from the vine during harvesting also creates high stress on the hands and wrist through high repetition (25-50 cuts per minute), which includes contact stress between the knife and hand Meyers et al, 2000]. On dairy farms, which have become highly automated, intense hand and arm motions are still required during the attachment of the milking machine to the utters of the cow [Stal, 2000]. These tasks are repeated twice a day, every day of the year for each cow on the farm.…”
Section: Upper Extremity Msds Risk Factorsmentioning
confidence: 99%
“…The combination of high hand force and repetitive hand exertions also occurs during pruning and harvesting at vineyards Meyers et al, 2000;. On many dairy farms where milking remains predominantly manual, intense hand and arm motions are still required (Stal, 2000). Even more-automated dairy operations require intensive handwork for attaching the milking devices to udders (Stal, 2000).…”
Section: Upper Extremities (Hands Wrists Elbows Arms and Shoulders)mentioning
confidence: 99%
“…The prevalence of hand or wrist MSDs is roughly 25%-30% in many subsectors of the agriculture industry (Pratt et al, 1992;Struttmann and Reed, 2002;Gomez et al, 2003). A Swedish study found that dairy farms may have one of the highest prevalence rates of hand/wrist injuries, exceeding 50% (Stal, 2000). Shoulder injuries and shoulder pain due to farmwork, although not as prevalent as hand/wrist injuries, happen often, with a yearly prevalence of about 7%-15% (equal to or greater than the rate associated with other manual labor, 9.7%) (Struttmann and Reed, 2002;Walker-Bone and Palmer, 2002).…”
Section: Upper Extremities (Hands Wrists Elbows Arms and Shoulders)mentioning
confidence: 99%
See 1 more Smart Citation